Augmentation Stability of Guided Bone Regeneration for Peri-Implant Dehiscence Defects with L-shaped Porcine-Derived Block Bone Substitute - Jae-Hong Lee (MDPI AG, 2021)
Block bone substitutes have better augmentation stability for guided bone regeneration (GBR) than particulate bone substitutes. This study sought to determine whether GBR with an L-shaped porcine block bone (DPBM-C) differs from GBR with an L-shaped bovine block bone (DBBM-C) based on clinical, radiographic, and volumetric outcomes for peri-implant dehiscence defects. A total of 42 peri-implant defects were grafted with 20 L-shaped DPBM-C and 22 DBBM-C groups. The horizontal and vertical thicknesses of the augmented hard tissue were measured using sagittal cone-beam computed tomography, and the volumetric tissue change was evaluated by stereolithography image superimposition. Postoperative discomfort, early wound healing outcomes, and implant stability were also assessed. Among the clinical (subjective pain and swelling, wound dehiscence, membrane exposure, and periotest values), radiographic (changes in horizontal and vertical hard tissue thickness), and volumetric parameters of the L-shaped DPBM-C and DBBM-C groups during the healing period, only the periotest values showed a statistically significant difference (0.67 ± 1.19, p = 0.042). Within the limitations of this study, an L-shaped DPBM-C is not inferior to an L-shaped DBBM-C based on their clinical, radiographic, and volumetric outcomes for GBR of peri-implant dehiscence defects.